The Likelihood of Exit for Russian Insiders: Initial Public Offerings Versus Mergers and Acquisitions - Denis SELEZNEV; Elena ROGOVA; Daria KOCHETKOVA (Communications of International Proceedings, 2023)
The study explores the determinants of insiders’ exit strategy (the choice between going public or being acquired by a strategic investor) for companies based in Russia. Our main goal is to address the lack of research evidence on what factors impact this choice and therefore, to create a model that predicts the likelihood of going public. The methodology is based on regression analysis. The final sample contains 6556 merger and acquisition (M&A) deals and 352 initial public offering (IPO) corporate events over the period of 2000-2021. Findings can be summarized as follows. The likelihood of an IPO over an acquisition is greater for less risky companies from a financial standpoint. Firms of higher size are more likely to go public rather than to be acquired. The information asymmetry, measured by company’s age, has an inverted U-shaped relationship with the likelihood of public offering. Companies’ profitability provided mixed results concerning the probability of IPO. The findings of our study may have value for private investors, institutional investors, researchers, consultants, external analysts, and internal company analysts who can use them for predicting the strategic choice related to insiders’ exit. The exit decision is one of the most important corporate events in the lifecycle of the firm, which dramatically changes the future of its operations and corporate life. Hence, prediction of this decision helps to improve companies’ corporate governance and sustainability. Although the study focuses on Russia, its findings can be adjusted to other emerging markets with similar institutional settings.
Keywords: initial public offerings; mergers and acquisitions; exit mechanism; Russian companies.